Reconstruction of Culture and Islam: by Prof Mohammad Taqi Amini, (author); Z. A. Usmani (Translator); Lahore: Siddiqe-e-Akbar Academy, Sole Distributors; Amjad Academy, 40, Urdu Bazar, Lahore, 270 pp. (American Journal of Islam and Society, 1989)
Mohammad Taqi Amini is an erudite religious scholar and profoundthinker. He possesses an inquisitive mind which refuses to accept things attheir face value. He sets out to prove that the reconstruction of Islamic civilizationaims at striking a balance between the physical and the spiritual forcesinherent in men. He attempts an outline of the scheme of cultural reconstruction.Also, he mentions the effects and implications of Western civilizationon modern life and evaluates the impact of two conflicting ideologies.The author believes that for the manifestation of faith and the constructionof culture, the necessary good deeds are not mere rituals or outwardsigns of virtue. Good deeds, on the other hand, comprehend both the innerand outward facets of life and they comprehend the whole being of man.The inner life however, comes first; for without it a healthy community cannotcome into existence, nor can man's use of nature yield any common benefit.The author reveals that in the framework of Western civilizationmaterialism dominates, and materialism recognizes reason as the only sourceof knowledge. But according to the Islamic concept of cultural reconstruction,the spiritual dimension is the basis of everything and which recognizesthe combined guidance of reason, heart and revelation for the acquisitionof knowledge. In all spheres of life such a wholesome and all pervasive guidanceis needed. The guidance of one faculty is not enough.In Western culture, the essential nature of man is regarded as animalisticand therefore the nature of character is determined in terms of material powerand worldly gains. Only those qualities are valuable which have a direct bearingon worldly gains and material power. For example, in business, punctuality,patriotism, social sense, and natural interests are the criteria. On the otherhand, qualities which do not have any bearing on worldly gains are not valued.Rather, violation of these qualities is considered a merit. Qualities like modesty,chastity, affection, mutual friendship and love, caring for the family, generosityof heart, soft-heartedness, sincerity, humanity, and consideration for the rightsof others have no value for a Western mind.The Islamic scheme of cultural reconstruction, on the other hand, isbased on a Divine view of life. This view divides life into material and nonmaterialand insists that both are necessary for the perfection of humanity ...